The Effectiveness of SINTA RAMA (Singing Bowl Chakra Massage Therapy) in Alleviating Premenstrual Syndrome in Adolescents - I Gusti Agung Manik Karuniadi; Ni Made Dwi Ayu Martini; Pande Putu Novi Ekajayanti (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: 65% of female adolescents experience premenstrual syndrome. Premenstrual syndrome is a syndrome or collection of symptoms (somatic and affective) that occur in women 2-14 days before menstruation. Management to relieve premenstrual syndrome can be done pharmacologically and non-pharmacologically. Non-pharmacological methods that can be provided with complementary services that can stimulate the production of endorphin hormones. Endorphin hormones have a very large role in improving physical and emotional conditions in women and one technique that can be done to stimulate their production is singing bowls.Objectives: The purpose of this study was to determine the effectiveness of SINTA RAMA (Singing Bowl Chakra Massage Therapy) in Alleviating Premenstrual Syndrome in Adolescent Girls.Methods: This study used a quasi-experiment with a Non-Equivalent Control Group Design, with purposive sampling involving 64 female adolescents, 32 as the intervention group and 32 as the control group who met the inclusion criteria.Result : This study found that the average score before the intervention was 25.79 in the intervention group and 20.06 in the control group. In the intervention group, there was a significant difference before and after the intervention with a p value of 0.014 (from an average before 25.79 to 18.34), while the results of the posttest difference test of the intervention and control groups obtained a p value of 0.000 (with an average score of 18.34 in the intervention group and 21.44 in the control group). Effect sizes indicated a moderateto-large difference at pretest (d = 0.69) and a moderate difference at posttest (d = -0.51), suggesting the intervention meaningfully influenced the outcomes.Conclusions: Singing Bowl Chakra Massage Therapy (SINTA RAMA) is effective in reducing Premenstrual Syndrome in Adolescents.